Analisis Strategi Peningkatan Produktivitas Tenaga Kerja Pemanen Kelapa Sawit di PT. Karangjuang Hijau Lestari 1 - Muthmainnah, Sri Devi; Jumiati, Elly; Mubarak, Ahmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to formulate strategies for improving the productivity of oil palm harvest workers at PT. Karangjuang Hijau Lestari 1, North Kalimantan, by considering the company’s internal and external conditions. The research employed a quantitative descriptive approach using a census method involving 75 harvesting worker households. Data analysis was conducted by identifying economic, social, and work environment factors related to labor productivity, which were subsequently analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) matrix to determine the company’s strategic position. Furthermore, the Quantitative Strategic Planning Matrix (QSPM) was applied to prioritize the most appropriate strategies. The results indicate that the company is positioned in a strategic condition that requires optimization of internal strengths to respond to external pressures. The priority strategies recommended include continuous technical training in harvesting activities, improvement of work systems, and the implementation of performance-based incentives to sustainably enhance labor productivity.